2010
DOI: 10.1002/gcc.20808
|View full text |Cite
|
Sign up to set email alerts
|

miR‐29b and miR‐125a regulate podoplanin and suppress invasion in glioblastoma

Abstract: Glioblastoma is the most frequent and malignant brain tumor, characterized by an elevated capacity for cellular proliferation and invasion. Recently, it was demonstrated that podoplanin membrane sialo-glycoprotein encoded by PDPN gene is over-expressed and related to cellular invasion in astrocytic tumors; however the mechanisms of regulation are still unknown. MicroRNAs are noncoding RNAs that regulate gene expression and several biological processes and diseases, including cancer. Nevertheless, their roles i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
97
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 126 publications
(107 citation statements)
references
References 42 publications
8
97
0
2
Order By: Relevance
“…4 miRNA dysregulation is a common feature of neoplasia and numerous miRNAs have been characterized as oncogenes or tumor suppressors in many cancers including in glioblastoma (GBM). 3,[5][6][7][8][9][10][11] microRNA-134 (miR-134) has been implicated in the regulation of physiological and developmental processes. It was shown to promote mouse embryonic stem-cell differentiation, dendritogenesis, and stage-specific cortical development.…”
mentioning
confidence: 99%
“…4 miRNA dysregulation is a common feature of neoplasia and numerous miRNAs have been characterized as oncogenes or tumor suppressors in many cancers including in glioblastoma (GBM). 3,[5][6][7][8][9][10][11] microRNA-134 (miR-134) has been implicated in the regulation of physiological and developmental processes. It was shown to promote mouse embryonic stem-cell differentiation, dendritogenesis, and stage-specific cortical development.…”
mentioning
confidence: 99%
“…In addition, results from the wound‐healing assay revealed that transfection of miR‐29b‐3p mimic significantly prevented the repair of cell scratch injury, suggesting the reduction of damage repair capacity of these cell types. Although no direct evidence shows miR‐29b‐3p could accelerate chondrocyte apoptosis at present, the inducing effect of miR‐29 family on apoptosis and cell cycle arrest has been described in a variety of tumour cell types and some normal cell types, including chronic myelogenous leukaemia cells 29, glioblastoma cells 30, neuronal cell 31 and multiple myeloma cells 32, and the mechanisms were usually associated with the regulation of BCR/ABL1, Mcl‐1, Bcl2. In this work, we observed that miR‐29b‐3p mimic could facilitate Bax expression, restrain Bcl2 expression and promote the activation of caspase‐3, which may contribute to the cell apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…PDPN expression enhances the motility and invasion of several transformed cell types including mammary carcinoma (7,8), glioma (28), and squamous carcinoma cells (29 -31). PDPN is found at the invasive front of many tumors, which is consistent with its role in promoting invasion (7,8).…”
Section: Discussionmentioning
confidence: 99%